Antibacterial, wearable, transparent tannic acid–thioctic acid–phytic acid hydrogel for adhesive bandages. Issue 14 (24th March 2022) - Shao, Xian-hui; Yang, Xiao; Zhou, Yue; Xia, Qing-chang; Lu, Yun-ping; Yan, Xiao; Chen, Chen; Zheng, Ting-ting; Zhang, Lin-lin; Ma, Yu-ning; Ma, Yu-xia; Gao, Shu-zhong
Abstract : Three naturally derived organic acids, namely tannic acid, thioctic acid and phytic acid, were used to fabricate a novel tissue adhesive hydrogel. Abstract : Making a hydrogel-based first-aid bandage with green resources, desirable biocompatibility, universal adhesive properties, low cost and simple production is a long-standing research aspiration. Considering this, three naturally existing organic acids, namely tannic acid, thioctic acid and phytic acid, were used to construct a novel adhesive gel (TATAPA hydrogel) for epidermal tissue bandage applications. This hydrogel could be synthesized under mild conditions with no need for a freeze–thawing shaping procedure, and was transparent, moldable and stretchable with good stability under continuous water immersion. In lap-shear tests, the TATAPA hydrogel could adhere to various hydrophilic and hydrophobic surfaces. Moreover, in the case of skin tissue adhesion, the hydrogel could be easily peeled off from the skin, meeting wearability requirements. Rheological tests showed that the hydrogel possessed thermal sensitive properties derived from multi-supramolecular interactions. The methicillin-resistant Staphylococcus aureus (MRSA)-infected burn wound test demonstrated that the hydrogel had desirable antibacterial activity and was beneficial for wound healing. A femoral artery bleeding assay was also used to reveal that the TATAPA hydrogel could be directly pasted onto the bleeding site for hemostasis. Overall, this hydrogel demonstrates potential as a surgical bioadhesive for a broad range of medical applications.